The politics of the new welfare states in Western Europe - Bonoli, Giuliano; Natali, David (San Domenico di Fiesole, 2011)
"The present paper has a twofold objective. First we discuss different possible interpretations of recent current social policy change. Western European welfare states have been characterised by (functional and normative) innovation towards cost-containment, activation, social investment, and the flexicurity model. While the effect of recent waves of reforms is still debated, norms and cognitive elements of welfare policy have clearly changed. Second, on the basis of existing scholarship, we try to develop an explanation of the observed pattern of change with specific reference to the politics of ‘blame avoidance’ and ‘credit claiming’. The recent reform process has seen the emergence of a complex set of strategies policymakers have implemented to improve social and political consensus for innovation. The latter has consisted in the transformation of the social and employment policies inherited from the past. Third we shed light on some key aspects of the reforms’ output and outcome, with a brief summary of the main issues in need for further research. Reforms have been consistent with the ‘contingent’ convergence of national welfare states through a sequence of transformative innovations, with evident distributional effects."